2008
DOI: 10.3758/mc.36.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Number of cues influences the cost of remembering to remember

Abstract: A current focus in the prospective memory literature is the extent to which a prospective memory task (remembering to perform a future action) interferes with ongoing activities (defined in this study as lexical decision latencies). In the present study, participants had to detect one, two, three, four, five, or six prospective memory cues. Results showed no significant increase in lexical decision latencies with one or two targets; however, significant costs emerged with three or more targets. Furthermore, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
125
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 23 publications
(45 reference statements)
16
125
6
Order By: Relevance
“…Thus, the present research converges with those studies examining task interference showing that, in the absence of monitoring (i.e., nonsignificant task interference), individuals may spontaneously retrieve their prospective memory intentions (A.-L. Cohen et al, 2008;Einstein et al, 2005, Experiments 1-4;Scullin et al, 2008). Notably, our paradigm for investigating spontaneous retrieval may have some advantages over the more traditional task interference approach.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…Thus, the present research converges with those studies examining task interference showing that, in the absence of monitoring (i.e., nonsignificant task interference), individuals may spontaneously retrieve their prospective memory intentions (A.-L. Cohen et al, 2008;Einstein et al, 2005, Experiments 1-4;Scullin et al, 2008). Notably, our paradigm for investigating spontaneous retrieval may have some advantages over the more traditional task interference approach.…”
Section: Resultsmentioning
confidence: 41%
“…On the other hand, if prospective memory retrieval is spontaneous and does not require monitoring for cues at the time the target event is encountered (and immediately preceding the target event), high prospective memory performance can be obtained in the absence of task interference (see the multiprocess theory; McDaniel & Einstein, 2000). The results of research testing for task interference have been mixed (A.-L. Cohen, Jaudus, & Gollwitzer, 2008;Guynn, 2003;Marsh et al, 2003;Smith, 2003;Smith & Bayen, 2004;Smith et al, 2007), suggesting that the parameters of the ongoing and prospective memory tasks may determine whether prospective memory retrieval requires that attentional resources be allocated to the prospective memory task immediately prior to target events (but see Smith et al, 2007, for an alternative explanation).…”
mentioning
confidence: 99%
“…For example, Cohen-Kdoshay and Meiran (2007) showed that their instructed flanker-compatibility effect disappeared with a concurrent load (see also Meiran & Cohen-Kdoshay, 2012). In a similar vein, Cohen, Jaudas, and Gollwitzer (2008) only observed automatic response activation of merely instructed S-R mappings with a restricted number of instructed mappings. This was confirmed by the results of an unpublished experiment that was conducted at our lab.…”
Section: Two Causes Of Task-rule Congruencymentioning
confidence: 88%
“…If having the intention to respond to a PM cue requires attentional resources, then fewer resources should be available to perform the ongoing task. In line with this rationale, ongoing-task performance is often significantly reduced (mostly in terms of slowing in reaction times [RTs]), when participants perform an ongoing task while holding an intention, as compared to participants who perform the ongoing task alone (Cohen, Jaudas, & Gollwitzer, 2008;Marsh, Hicks, & Cook, 2006b). The degree to which such task interference occurs depends on characteristics of both the ongoing task and the PM task such as the complexity of the ongoing task (Einstein, McDaniel, Williford, Pagan, & Dismukes, 2003) and the time of the occurrence of the PM cue (McBride, Beckner, & Abney, in press).…”
Section: Task Interference From Event-based Intentionsmentioning
confidence: 91%
“…In their first application of the diffusion model to PM data, Horn et al (2011) did not find effects on the t 0 component when comparing a PM task of medium demands (cf. Cohen et al, 2008) with a control group without a PM task. However, Horn and colleagues suggested that with further increased PM demands, participants might start checking for PM cues constantly on each trial in addition to their ongoing-task decision (Guynn, 2003), and these differences in cue checking might be reflected by the t 0 component.…”
Section: Discussionmentioning
confidence: 99%